Analytical Study of Babbitt/steel Composite Structural Bars in Oblique Contact-impact with a Solid Flat Surface - Y. Wang; Z. Fu (Mechanical Sciences, 2019)
The oblique contact-impact characteristic of the composite structural bar composed of Babbitt alloy and low-carbon steel (ZChSbSb11-6 ∕ AISI 1020) with a solid flat surface (AISI 1045) was studied theoretically and experimentally. The dynamic equation of the composite structural bar with vibration response during the contact-impact was established using the momentum theorem and assumed mode method, and the instantaneous contact forces during different impact phases were analyzed based on modified Jackson–Green model. Four sets of experiments (i.e. different proportion of Babbitt, ξ={1/8,1/2,3/4,7/8}<svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="117pt" height="14pt" class="svg-formula" dspmath="mathimg" md5hash="248786ae5e506bfa15814448c87716e2"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="ms-10-213-2019-ie00001.svg" width="117pt" height="14pt" src="ms-10-213-2019-ie00001.png"/></svg:svg>) for the initial angle, θ=45∘<svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="38pt" height="11pt" class="svg-formula" dspmath="mathimg" md5hash="3e14a05886fd58eec4fc0a4526a8bc0a"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="ms-10-213-2019-ie00002.svg" width="38pt" height="11pt" src="ms-10-213-2019-ie00002.png"/></svg:svg>, and different initial velocities were performed; and, the rebound linear and angular velocity of the contact point of composite structural bar after impact was calculated and compared with experimental results. Besides, the coefficient of restitution, the relation of contact force and contact deflection, and the permanent deformation were also compared for the composite structural bars with different proportions in combination, ξ. Three critical angles are found to determine whether the composite bar slides or not, but are prominently different for the composite bars with different ξ. In comparing with the experimental results, the numerical solutions of rebound linear and angular velocity had yield encourage results and, all relative errors were small, indicating that the simulations are in good agreement with the experimental results. Also, the oblique contact-impact behavior involving the coefficient of restitution, the relation of contact force and contact deflection, and the permanent deformation was explained in detail. It can be concluded that as the proportion of Babbitt ξ increases, the composite structural bar presents a characteristic of ease of deflection. And the contact-impact behavior of structural entity is closely related to the inherent properties of the elasto-plastic material, especially for the weak material of composite structures. The more easily the impacting object is deformed, the small the contact force during the contact-impact, which also indicates the yield strength of weak material is a very significant parameter in the event of collision. Such work could give conducive insights to contact-impact problems of the key parts or structures composed of composite materials in mechanical system.